A modified rat model of exercise-induced renal injury and the protective effects of losartan and Yishen Huanji decoction. (August 2013) - Chen, Hong; Zhou, Chun-Hua; Yang, Jun
Abstract We modified a rat model of exercise-induced renal injury by forcing 4-week-old male Sprague-Dawley (SD) rats (the MOD group) running on a treadmill for 8 weeks under conditions of high temperature, high humidity, bearing weight with some additional stimulations. Compared with the control (CON) group, the traditional running group (TRA), the losartan potassium intervention running group (LOS) and the traditional Chinese medicine "Yishen Huanji Decoction" intervention running group (CHI), the urinary, biochemistry indicators, the concentrations of angiotensin II (Ang II) were significantly higher in the MOD group than in the TRA group. After 3--4 weeks and 8-week training program, the 24-h urine protein and NAG levels in the LOS group and CHI group were lower than in the MOD group respectively. The BUN and SCr levels in the CHI group were lower than in the MOD group and higher than in the LOS group. AngII concentrations in the LOS group were higher than the MOD group. The modified rat renal injury model induced greater lesions than the traditional model. High temperatures, humidity and weight bearing were critical factors to induce Ang II activation, which can aggravate renal injury. Losartan potassium and the "Yishen Huanji Decoction" can protect against renal injury.